School level and urbanicity differences in drilled plans for evacuation, lockdown, and shelter-in-place scenarios: A national analysis - McAlpin, David S; Lunenburg, Frederick C; Slate, John R (American Journal of Education and Learning, 2023)
The purpose of this article was to determine the degree to which differences were present in drilled school safety plans by school level and urbanicity for the 2015-2016 and 2017-2018 school years. Data from a national survey were analyzed. As such, a causal-comparative or ex post facto research design was present. Inferential statistical analyses of nationwide survey data revealed the presence of statistically significant differences in the incidence of drilled school safety plans. Elementary schools were fourth less likely to perform shelter-in-place drills than were high schools. More than three times as many schools located within a suburb performed lockdown drills at a more significant rate than schools in rural settings. Given the recent school violence tragedies, implications for all schools having written plans and, more importantly, having drilled their students and teachers in those plans are present. Recommendations for future research studies were discussed.